Twisted Paths and Strange Forms: Visuality as a Tool for Controlling Demons - Sofer, Gal (Mabatim: Journal of Visual Culture, 2022)
In many treatises concerned with methods of summoning demons, readers encounter detailed physical descriptions of the entities invoked. At times, these textual descriptions are accompanied by visual representations, some of which are explicitly intended to exert control over the summoned demons. This article examines several such interrelated treatises and discusses the visual dimensions they contain. What role do these visual aspects play within the texts? Do they serve a purely aesthetic function? The study argues that close reading of these sources compels us to consider the inherent power of visual representations and the ways in which they were employed in the practices of summoning and controlling demons.